2011
DOI: 10.1007/s00520-011-1259-9
|View full text |Cite
|
Sign up to set email alerts
|

Switching from oxycodone to methadone in advanced cancer patients

Abstract: Purpose The aim of this study was to prospectively evaluate the outcomes and the conversion ratio of switching from oxycodone to methadone in advanced cancer patients admitted to an acute palliative care unit. Patients and methods A prospective study was carried out on a cohort of consecutive sample of patients receiving oxycodone, who were switched for different reasons mainly because of an inconvenient balance between analgesia and adverse effects. An initial conversion ratio between oxycodone and methadone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 16 publications
0
8
0
2
Order By: Relevance
“…Some studies have used protocol-defined cutoff points for pain and adverse effect intensity to determine opioid dosing and switching. 14,20 In this study, there was a wide range of reported analgesic and side-effect scores in both opioid responders and nonresponders. It is thus difficult, if not impossible, to choose specific thresholds to define opioid response because of the high variability within the study population, a finding mirrored in other studies.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Some studies have used protocol-defined cutoff points for pain and adverse effect intensity to determine opioid dosing and switching. 14,20 In this study, there was a wide range of reported analgesic and side-effect scores in both opioid responders and nonresponders. It is thus difficult, if not impossible, to choose specific thresholds to define opioid response because of the high variability within the study population, a finding mirrored in other studies.…”
Section: Discussionmentioning
confidence: 95%
“…These assessments were in line with other studies in this area. 20,21 Pain was assessed using the Brief Pain Inventory, 22 which is validated and widely used. For each of the five pain modalities, …”
Section: Assessmentsmentioning
confidence: 99%
“…These patients have been referred to as ‘morphine non‐responders’[109]. A similar pattern of response variability is seen with other strong opioids [110–112]. Clinical experience and a number of studies have demonstrated variability in terms of the level of analgesia achieved, the side effects experienced and the daily dose of opioid required.…”
Section: Clinical Perspectivesmentioning
confidence: 96%
“…Penelitian lainnya Mercadente dkk. 15 menunjukkan VAS pada tiap-tiap kelompok tidak berbeda bermakna pada nyeri kanker pankreas. Hal yang sama juga menunjukkan tidak ada perbedaan antara morfin dan oksikodon terhadap nyeri sedang sampai pasien kanker.…”
Section: Tabel 4 Perbedaan Nilai Vas Antara Kelompok Morfin-cr Dan Keunclassified